Integration of AI Chatbot as an Interactive Companion in Foreign Language Learning in High School - Jihad, Adriani; Mulyani, Mulyani (Yayasan Pendidikan Islam Daarut Thufulah, 2025)
Background. Advances in artificial intelligence (AI) technology have opened up new opportunities in the field of education, especially in learning foreign languages at the high school level. However, the integration of AI-based chatbots as interactive companions in the context of formal learning is still rarely explored, especially in Indonesia. The main problems faced in learning foreign languages are limited interaction time and low confidence of students in using the target language. Purpose. This study aims to evaluate the effectiveness of the use of AI chatbots as an interactive learning partner in improving the outcomes and quality of foreign language learning of high school students. The main focus is directed at improving academic performance, motivation, and student engagement through adaptive and personalized digital interactions. Method. The research method used was a quasi-experimental design with two groups, namely the experimental group that used chatbots and the control group that learned by conventional methods. The research instruments included pretest and posttest tests, engagement questionnaires, and observation of student learning behavior. The sample consisted of 60 grade XI students at one of the State High Schools. Results. The results showed a significant increase in the posttest scores of the experimental group compared to the control group. In addition, chatbots also play a role in building confidence and increasing students' active participation in foreign language practices independently. Conclusion. The conclusion of this study states that AI chatbots are effective as an interactive companion that is able to enrich the experience of learning a foreign language. The uniqueness of this research lies in the integration of chatbots in the formal curriculum of high schools, as well as its contribution in answering the needs of personalized learning through AI-based technology.